Determination of Radio Refractive Index using Meteorological Data - Valma, E.; Tamošiūnaitė, M.; Tamošiūnas, S.; Tamošiūnienė, M.; Žilinskas, M. (Elektronika ir Elektrotechnika, 2010)
The International Telecommunications Union – Radiocommunications (ITU–R) model was used for calculation of the radio refractive index according to the peculiarities of climatic conditions in Lithuania. For the first time the radio refractive index for different localities in Lithuania have been determined using this model. The values of the radio refractive index have been determined at altitude by starting from 6 m up to 162 m above the sea level in the troposphere. The daily and the seasonal variations of the radio refractive index – value have been determined. It was obtained, that the maximum values of radio refractivity are in Klaipėda and Kaunas and the minimum one was determined in Vilnius. The obtained data was compared with the known value of average atmospheric radio refractive index close to the ground surface at the standard atmosphere conditions and with ones measured in neighbour state Latvia.